Boyle Heights : how a Los Angeles neighborhood became the future of American democracy - Sanchez, George J. (University of California Press, 2021)
"This is a history of a Los Angeles community that represents cross-cultural possibility in America's future. The history of Boyle Heights tells an important story of neighborhood strength because of its diversity and a constant stream of newcomers to Los Angeles, who become absorbed into the life of the city in ways that were both accommodating and complicated. It is clear that the residents of the neighborhood developed a unique identity that set them apart from the rest of the city, even while intense racialization was occurring among the various groups that made up the local population. Migrants to the United States learned what it meant to be American in Boyle Heights, as newcomers to Los Angeles learned what it meant to be Angelino. Even as the neighborhood changed dramatically over time because of larger racial and economic forces that fostered concentrated poverty and other unstable life conditions, a communal and progressive spirit prevailed in Boyle Heights that continued to define the promise of the American dream for all who lived there. This book is organized chronologically, with each chapter focusing on the interaction between different groups that made up the Boyle Heights population"-- Provided by publisher
Keywords: Neighborhoods -- California -- Los Angeles -- History.; Boyle Heights (Los Angeles, Calif.) -- History.; Boyle Heights (Los Angeles, Calif.) -- Race relations -- History.; SOCIAL SCIENCE -- Sociology -- Urban.; Neighborhoods; Race relations; California -- Los Angeles; California -- Los Angeles -- Boyle Heights; History